Variation in survival and stem quality of Douglas-fir provenances: Insights from 47-year-old common garden experiments in Romania - Stoica Emanuel; Alexandru Alin; Mihai Georgeta; Curtu Alexandru (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
Understanding the genetic variation of wood quality traits is essential for developing breeding strategies to improve the quality of Douglas-fir plantations. This study assessed the performance of 61 Douglas-fir provenances established in 1977 established in three Romanian common garden experiments (Aleșd, Făget and Padeș). A mixed linear model was applied to estimate the variance components, and Pearson correlations were used to explore trait relationships. The results revealed significant provenance effects for branch angle, branch diameter, number of branches, and survival at Aleșd, and for branch angle and diameter at Făget. Survival and branch traits, particularly branch angle and diameter, were the most stable traits across the field trials and hence suitable for early selection and breeding across similar site conditions. Over 50% of trait variance was accounted by stem form, forking index, and number of branches due to strong environmental effects. Provenance-by-environment interaction was significant only for branch diameter, suggesting that this trait is more sensitive to site-specific conditions. The other traits had stable provenance rankings across environments due to non-significant interaction effects. These findings highlight the potential to use selected provenances as a genetic base for renewing the Douglas-fir breeding program in Romania. Selecting provenances with high survival and favourable branch traits improves timber quality and plantation resilience. The study also demonstrates the relevance of long-term provenance trials in identifying climate-resilient genetic resources, which is critical for maintaining forest productivity and stability under future climate change scenarios.